Peran Kompetensi Pedagogik Guru PPPK dalam Meningkatkan Kualitas Pembelajaran: Studi Kasus di SMP Negeri 1 Talangpadang - emawati; Fatqul Hajar Aswad; M. Badrun; Siswoyo (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze in depth the role of pedagogic competence of teachers of Government Employees with Employment Agreements (PPPK) in improving the quality of learning at SMP Negeri 1 Talangpadang, Tanggamus Regency, Lampung Province. Using a qualitative approach of the case study type, this study involves PPPK teachers, school principals, and students as informants. Data collection techniques were carried out through in-depth interviews, classroom observations, and documentation studies. Data analysis uses the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that although PPPK teachers have conceptual mastery of pedagogic aspects such as planning, implementation, and evaluation of learning, the level of implementation is still uneven. The main obstacles faced include the absence of post-placement training, lack of reflective academic supervision, and limited supporting technology facilities. However, in general, PPPK teachers have been able to maintain the quality of basic learning, although it is not optimal in creating innovative, adaptive, and Independent Curriculum-based learning. This research emphasizes the urgency of strengthening a contextual and sustainable professional coaching system for PPPK teachers, in order to maximize their contribution to improving the quality of education in public schools, especially in non-urban areas.